2022
DOI: 10.3390/cancers14174209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Strategies Targeting the Tumor Microenvironment of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic cancer has a complex tumor microenvironment which engages in extensive crosstalk between cancer cells, cancer-associated fibroblasts, and immune cells. Many of these interactions contribute to tumor resistance to anti-cancer therapies. Here, new therapeutic strategies designed to modulate the cancer-associated fibroblast and immune compartments of pancreatic ductal adenocarcinomas are described and clinical trials of novel therapeutics are discussed. Continued advances in our understanding of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 304 publications
1
16
0
Order By: Relevance
“…Thus, a node’s degree is not the sole determinant of its essentiality, rather, it depends on the topological position of that node. This is reflected in our results, where, F2RL1, F10, APOC2, CLDN2, PCDH1 which has quite a low degree (4,4,8,11,3) respectively in the primary network, found out to be RGs based on its ability to make it to the last level of the organization. F2RL1 formed a motif in the last level of the organization with another KR, MMP1 , which has a fairly high degree (36) in the primary network.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, a node’s degree is not the sole determinant of its essentiality, rather, it depends on the topological position of that node. This is reflected in our results, where, F2RL1, F10, APOC2, CLDN2, PCDH1 which has quite a low degree (4,4,8,11,3) respectively in the primary network, found out to be RGs based on its ability to make it to the last level of the organization. F2RL1 formed a motif in the last level of the organization with another KR, MMP1 , which has a fairly high degree (36) in the primary network.…”
Section: Resultssupporting
confidence: 69%
“…Immunotherapy with immune checkpoint inhibitors has shown promise in PDAC, particularly in tumors harboring mismatch repair deficiency (dMMR) and high microsatellite instability (MSI-H) (10). The presence of a dense fibrotic stroma in PDAC creates a physical barrier around the cancer cells, hindering drug delivery and promoting tumor growth and treatment resistance (11). Advances in surgical approaches, immunotherapeutic approaches, and targeted therapies are being explored to overcome the treatment refractory nature of PDAC and improve patient outcomes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their ability to release high amounts of ECM proteins and immune regulatory mediators, HMF generate a dense stroma, which acts as a physical barrier for immune cells and drugs ( 12 ). Although several studies have already demonstrated that myofibroblasts essentially contribute to drug resistance and immune evasion in PDAC ( 15 17 ), their impact on immune evasion of PDAC liver metastases is still poorly understood. Since metastases are not routinely resected in PDAC patients, tissue samples from PDAC metastases are rare and the expression of immune regulatory molecules such as PD-L1 within liver metastases is rarely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, CAFs and the extracellular matrix (ECM), impressive features of the PDAC TME, were the most frequently reviewed and discussed [28][29][30][31][32][33][34]. Functional heterogeneity of CAF subtypes was repeatedly described: some might be tumor-promoting, while others might be tumor-suppressive.…”
mentioning
confidence: 99%
“…Skorupan et al overviewed the recent and current clinical trials of immune-modulating agents and stroma-targeting agents and described the potent combination of targeting PDAC cells with TME modulation [31]. Wang et al overviewed ECM physiology in a healthy status as well as in PDAC, and discussed the crucial roles of ECM, focusing on its influence on the cancer stem cell property [32]. Heger et al analyzed the PDAC stroma after neoadjuvant chemotherapy (NAC) and documented a better prognosis of the patients with low α-smooth muscle actin density, suggesting a difference from the patients who underwent upfront surgery [33].…”
mentioning
confidence: 99%